Frequency Analysis of Maximum Daily Rainfall for Flood Risk Management in Jazan Province Kingdom of Saudi Arabia: Excel-Based Model - Farran, Mohammed (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2025)
The Kingdom of Saudi Arabia (KSA) is one of the most arid countries in the world, rainfall is almost rare except for the southwestern area of KSA, where the Jazan Province is located. The study aims to analyze rainfall distribution to find out the appropriate distribution for the Jazan Province through annual rainfall data for the Jazan Province to provide a database for hydrological studies and flood risk assessment. The data of 25 rainfall stations were used for periods ranging from 19 to 59 years (1960-2018) for the average annual rainfall and the daily maximum. An Excel sheet has been prepared with the distributions used (log-normal, Pearson type III, log-Pearson type III, GEV, and Gumbel) in the analysis (model). Based on the RMSE criterion, the results showed that the GEV distribution is the best probability distribution for 36% of stations. Followed by distributions log-Pearson III, Gumbel type I, log-normal, and Pearson type III with percentages of 32%, 16%, 12%, and 4% of the total studied stations, respectively. The model showed effectiveness in the analysis, as its results were validated by the Hyfran Plus program, it is recommended to use the model.